Big and little gastrin responses to food in normal and ulcer subjects. Issue 11 (November 1979) - Taylor, I L; Dockray, G J; Calam, J; Walker, R J
Abstract : In normal, duodenal ulcer, and gastric ulcer subjects the two main forms of gastrin, G17 and G34, were estimated by radioimmunoassay in fasting serum and after feeding. Two antisera were used: one showing high specificity for G17, the other specific for the common COOH-terminus of G17 and G34 and so allowing estimation of G34 by difference. Basal G17 was similar in gastric ulcer, duodenal ulcer, and normal subjects and the increases of G17 after feeding were also similar in these groups. In contrast, basal G34 was similar in normal and duodenal ulcer subjects but raised in gastric ulcer subjects. After a meal the G34 concentration in both gastric and duodenal ulcer patients was significantly higher than normal. It is concluded that the higher post-prandial gastrin responses in peptic ulcer that have been previously described are due largely to increased G34.